PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK PEMBELAJARAN MATA KULIAH PENDIDIKAN KESEHATAN SEKOLAH BAGI MAHASISWA PRODI PJKR FIK UNY - Sismadiyanto Sismadiyanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
The aims of this research and development was to produce a learning software in the form of Compact Disc (CD) for a course namely school health education. This interactive CD was expected to be used for dealing with the limitation of learning resources and to help students in understanding the course materials, improving apreciation, motivation, and independencies. This research is research and development. The method employed in this research was descriptive procedural by which the development of the product follows the supposed procedures to produce a product. There were three basic steps that should be taken by the developer; they were problem conceptualization, product making, and product trial. The population of this research was students at semester 3 Physical Education, Health, and Recreation Program of Study at UNY taking School Health Education Class. This research employed descriptive statistics in analyzing the data. The final result of this research was an interactive CD that could be used for teaching and learning in School Health Education class. The contents developed in the CD were (1) youth health reproduction, (2) healthy environment, (3) healthy lifestyle and the effects of smoking, drinking, and abusing drug, (4) healthy eating behavior and balanced menu concept. Kata Kunci: Pengembangan Multimedia Interaktif, Mata Kuliah Pendidikan Kesehatan Sekolah pt'F ddXu(%n Jasmani Olahraga dan Kesehatan, Perkembangan Gerak, Keterampilan Sosial